Learnings from/about diversity in space and time: discursive constructions in the semiotic landscape of a teacher education building in Norway - Sollid, Hilde; Hiss, Florian; Pesch, Anja Maria (International Journal of Multilingualism, 2023)
This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. This article critically examines the discourses concerning historicaland transnational linguistic and cultural diversity in the semioticlandscape of a new teacher education building in Norway. In2020, this building, housing the Department of Education,opened at UiT The Arctic University of Norway, in the city ofTromsø. Designing, constructing, and decorating a new buildingfor a national teacher education was taken as an opportunity toreflect on and negotiate the institution’s role in relevantcontemporary, as well as historical, educational discourses and tomark a current standpoint. Taking a nexus analytical approach,we analyse how linguistic and cultural diversity are representedin the department’s public space and how this is interwoven withthe construction of the institution’s position in a multilingual andmulticultural environment. Our analysis shows that this diversityis constructed through various contrasts. Sámi identities andregional roots of knowledge are emphasised in the official part ofthe semiotic landscape–framed as learnings from diversity.However, by analysing meta-sociolinguistic discourses aboutdiversity, we show that this is accompanied by the erasure ofother aspects of linguistic and cultural diversity, in particular Kvenculture and identity, transnational diversity, and children andtheir lifeworld. publishedVersion